INVESTIGATING EFL LEARNERS’ READING DIFFICULTIES AND THE POSSIBLE SOLUTIONS - Devi Nurhayati; Reno Julyan; Aldha Williyan (PRODI PENDIDIKAN BAHASA INGGRIS INSTITUT PENDIDIKAN DAN BAHASA INVADA, 2023)
This study investigates the reading difficulties faced by EFL learners and proposes possible solutions for English Education students in an Indonesian university. Reading comprehension is a vital component of the English education curriculum, as it enables students to comprehend and analyze texts effectively. To conduct this study, a descriptive strategy was employed in combination with a qualitative approach. The questionnaire was designed to identify common challenges encountered by students, including difficulties in text translation, enhancing motivation, and the teaching methods employed by instructors. Data was collected through interview sessions, questionnaire responses, and documentation. The findings revealed that students predominantly struggled with sentence comprehension. By addressing these issues and fostering a desire to read, related challenges such as limited vocabulary, grammar proficiency, and sentence interpretation can be effectively tackled. Moreover, some students faced difficulties arising from inadequate teaching methods employed by their instructors. Consequently, this study concludes that students' reading difficulties primarily revolve around understanding the text itself, which in turn leads to other complications such as grammar mastery, vocabulary limitations, and text translation problems. These factors emerge from both students themselves and the instructional approaches adopted by their teachers.